Long term and repeated electron microscopy and PCR detection of Borrelia burgdorferi sensu lato after an antibiotic treatment - Honegr, K; Hulínská, D; Beran, J; Dostál, V; Havlasová, J; Cermáková, Z (Central European journal of public health, 2004)
The diagnosis of Lyme disease in 18 patients has been proved by detection of Borrelia burgdorferi sensu lato when using immunoelectron microscopy or detecting its nucleic acid by PCR in the plasma or the cerebrospinal fluid. The positive results occurred in the plasma or in the cerebrospinal fluid in the period of 4-68 months after an antibiotic treatment. The typical clinical manifestations of Lyme disease were observed in 9 patients and non-specific symptoms in another 9 patients. According to presented results we can recommend repeated examination using PCR of the plasma and other biological specimens in the individuals with persistent or recurring complaints after an acute form of Lyme disease and its antibiotic treatment. Also examination of the cerebrospinal fluid with non-specific symptoms and simultaneously displayed pathology electroencephalogram and/or magnetic resonance imaging findings can be advantageous.
Keywords: Borrelia burgdorferi komplex; Immunoglobulin G; lymeská nemoc; polymerázová řetězová reakce; Male; Microscopy, Immunoelectron; Immunoglobulin M; Adolescent; Lyme Disease; western blotting; imunoglobulin M; Česká republika; Child; antibakteriální látky; dítě; Adult; imunoglobulin G; dospělí; mužské pohlaví; Borrelia burgdorferi Group; mladiství; Czech Republic; Time Factors; Blotting, Western; DNA, Bacterial; DNA bakterií; lidé; ženské pohlaví; Anti-Bacterial Agents; Humans; imunoelektronová mikroskopie; časové faktory; Polymerase Chain Reaction; Female; lidé středního věku; Middle Aged